A Multi-Country Comparison of User Innovation Behaviors on Smartphone Applications - Bosul Yoo; Sotaro Katsumata; Takeyasu Ichikohji (International Telecommunications Society (ITS), 2017)
This study examines preceding factors of user innovation behavior using a case of smartphone applications toexamineindirect and direct effects of consumer attitude on user innovation. Specifically, this study focuses ontwo aspects of the user innovation evaluation:quality and quantity. Quality of user innovation in particular has the potentialtocontribute tothe profitability of firms thatprovide social mediaor other community services.This study proposes a structural model to examine the relationship between thesetwo user innovation aspects and preceding attitude factors, involvement, consumer knowledge,and customer orientation.The empirical analysisis based ona consumer survey to examine commonalitiesand differences in two countries: Japan and China. In each country, two services are chosen asrepresentative cases of the user-generated content business modelto measure user innovation behaviors based on the two aspectsmentioned.Byclarifying the preceding factors of user innovation behavior, this study hasimplications for new business models and future innovation research.
Keywords: M31; M15; O30; 330; User Innovation; Smartphone Applications; UGC (User-Generated Content); Customer Orientation